À la redécouverte d’un paysage hydroélectrique stratifié, entre montagne et plaine - Viviana Ferrario; Amelia Maris (Projets de Paysage)
The development of hydro-electric energy during the whole of the 20th century often transformed alpine valleys into areas specialised in the generation and distribution of energy. These “electric landscapes” were sometimes layered upon landscapes resulting from other systems for exploiting resources. In other instances they replaced these systems or even caused their disappearance. By specialising in the generation of energy some of these territories became vulnerable. This was the case of the Val Lapisina. Literally transformed in the 20th century into an infrastructural corridor-landscape it is now experiencing significant social and economic decline. The article proposes an interpretation of the strata of the area’s hydro-electric landscape and of the outlying landscapes. The aim is to provide a better understanding of these landscapes and to make it possible to project a different future in which their assimilation as a heritage and the development of tourism around the hydro-electric infrastructures can provide new development opportunities.